Adsorption of heavy metal from aqueous solution by dehydrated root powder of long-root Eichhornia crassipes. Issue 2 (1st February 2016) - Li, Qiang; Chen, Bo; Lin, Peng; Zhou, Jiali; Zhan, Juhong; Shen, Qiuying; Pan, Xuejun
Abstract: The root powder of long-root Eichhornia crassipes, as a new kind of biodegradable adsorbent, has been tested for aqueous adsorption of Pb, Zn, Cu, and Cd. From FT-IR, we found that the absorption peaks of phosphorous compounds, carbonyl, and nitrogenous compounds displayed obvious changes before and after adsorption which illustrated that plant characteristics may play a role in binding with metals. Surface properties and morphology of the root powders have been characterized by means of SEM and BET. Energy spectrum analysis showed that the metals were adsorbed on root powders after adsorption. Then, optimum quantity of powder, pH values, and metal ion concentrations in single-system and multi-system were detected to discuss the characteristics and mechanisms of metal adsorption. Freundlich model and the second-order kinetics equation could well describe the adsorption of heavy metals in single-metal system. The adsorption of Pb, Zn, and Cd in the multi-metal system decreased with the concentration increased. At last, competitive adsorption of every two metals on root powder proved that Cu and Pb had suppressed the adsorption performance of Cd and Zn.